ASPECTS OF THE FINANCIAL RISK IN THE ROMANIAN ECONOMY VERSUS THE FRENCH ECONOMY - COMPARATIVE PERSPECTIVE AND ANALYSIS - Marinela BARBULESCU; Alina HAGIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2016)
Financial risk is characterizing the variability of outcome indicators within the subject of the company's financial structure. A firm's capital structure is: equity and borrowed capital. In the first part of the paper we presented the types of risks that surround us in contemporary economic life, followed by the detailing and analyzing financial risk at the Romanian enterprise level, and in the last part we applied practically the fundamental financial analysis of risk on the French model. The aim of this paper was to present and analyze the most important situations in which the risk is presented in the economy and to offer suggestions and methods by which it’s unwanted effects can be avoided, minimized or controlled, so as to improve human performance.